Lightweight and Scalable Intrusion Trace Classification Using Interelement Dependency Models Suitable for Wireless Sensor Network Environment - Dae-Ki Kang (International Journal of Distributed Sensor Networks)
We present a lightweight and scalable method for classifying network and program traces to detect system intrusion attempts. By employing interelement dependency models to overcome the independence violation problem inherent in the Naive Bayes learners, our method yields intrusion detectors with better accuracy. For efficient and lightweight counting of n -gram features without losing accuracy, we use a k -truncated generalized suffix tree ( k -TGST) for storing n -gram features. The k -TGST storage mechanism enables us to scale up the classifiers, which cannot be easily achieved by Support-Vector-Machine- (SVM-) based methods that require implausible computing power and resources for accuracy. Experimental results on a set of practical benchmark datasets show that our method is scalable up to 20-gram with consistent accuracy comparable to SVMs.